Effectiveness of the transcultural nursing model on nutritional care and patient satisfaction in a multicultural hospital in Maluku, Indonesia - Rony A. Latumenasse; Hetti Marlina Pakpahan; Tati Setyawati Ponidjan; Wulida Litaqia (AcTion: Aceh Nutrition Journal, 2026)
Multicultural hospitals face challenges in providing nutritional care that accommodates patients’ cultural beliefs and dietary practices. This study aimed to evaluate the effectiveness of the transcultural nursing model in improving nutritional care and patient satisfaction in a multicultural hospital setting in Japan. A quasi-experimental pretest–posttest control group design was conducted at a Type B Regional General Hospital in Ambon, Maluku Province, Indonesia, from January to April 2025. A total of 120 adult inpatients were randomly assigned to an intervention group receiving culturally tailored nutritional nursing care based on Leininger’s Transcultural Nursing Model and a control group receiving standard nursing care. Data were collected using the Nutritional Care Satisfaction Scale (NCSS) and the Patient Satisfaction with Nursing Care Quality Questionnaire (PSNCQQ) and analyzed using parametric statistical tests with a significance level of p < 0.05. The intervention group demonstrated significantly greater improvements in nutritional care satisfaction and overall nursing care satisfaction than the control group (p < 0.01; Cohen’s d > 1.7). In conclusion, these findings indicate that the transcultural nursing model effectively enhances culturally sensitive nutritional care and patient satisfaction in multicultural hospital settings.